2006
DOI: 10.1111/j.1469-7998.2006.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Scent marking and territorial defence in male bushbuck (Tragelaphus scriptus)

Abstract: Tragelaphine antelopes were often considered to lack territoriality. A recent study, however, has suggested that male bushbuck Tragelaphus scriptus use the inner core of their home ranges exclusively. In this study, we examined whether males demarcate this area with an oily secretion emanating at their horn bases and cheeks (front rubbing). Furthermore, we studied aggressive interactions between adult males relative to home-range dimension. We found that the distribution pattern of the nearest-neighbour distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…Since small antelopes need to feed on high quality browse in a habitat with limited resources available to ground level ungulates, territoriality should be selected in order for the animals to be able to obtain sufficient resources for themselves and their offspring (Jarman 1974(Jarman , 1983Eisenberg and McKay 1977). When females are sedentary, males may be territorial in order to defend access to these females (Wronski et al 2006b). However, territoriality is still found in small antelopes that live in more open habitat, which may also relate to genetic or life history attributes (Brashares et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since small antelopes need to feed on high quality browse in a habitat with limited resources available to ground level ungulates, territoriality should be selected in order for the animals to be able to obtain sufficient resources for themselves and their offspring (Jarman 1974(Jarman , 1983Eisenberg and McKay 1977). When females are sedentary, males may be territorial in order to defend access to these females (Wronski et al 2006b). However, territoriality is still found in small antelopes that live in more open habitat, which may also relate to genetic or life history attributes (Brashares et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Male, but not female, grey duikers also counter-marked introduced dung (Lunt et al 2006).The fact that males also counter-marked female dung could represent intersexual communication or mate guarding. In the bushbuck, males counter-marked female dung more than male dung in latrines, which were thus considered to be primarily sites for intersexual communication, in which females signal and males respond (Wronski et al 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…In the study area, females are almost equally distributed, so males cannot monopolize female aggregations. However, females have relatively small home ranges (90% MCP, mean±SD: 0.15±0.13 km 2 ) and adult male home ranges (90% MCP, mean±SD: 0.68± 0.25 km 2 ) can encompass several female home ranges (Wronski 2004;Wronski et al 2006b). …”
Section: Discussionmentioning
confidence: 99%
“…The most plausible explanation of why the bushbuck has been so little investigated is its cryptic lifestyle. Adult males defend the inner core of their home ranges against other males, indicating that the males at least are indeed territorial (Wronski 2005;Wronski et al 2006a). Our own studies have revealed that both male and female bushbuck are sedentary and occupy well-defined home ranges (Wronski 2005;Wronski and Apio 2006;Wronski and Plath 2006).…”
Section: Introductionmentioning
confidence: 92%
“…If this were true, a major prediction would be that adult territory holders would show these behaviours more often than young-adult bachelors or subadult males. While performing front-rubbing, bushbuck males rub their horns, foreheads, cheeks and necks on objects such as twigs, leafs and branches (Estes 1991;Jacobsen 1974;Kingdon 1982;Wronski et al 2006a). On occasion, these secretions seem to be the source of considerable irritation, since flies are particularly attracted to them, and bushbuck have been frequently observed shaking their heads and dashing into dense cover in a deliberate attempt to avoid the flies (Kingdon 1982;T.…”
Section: Introductionmentioning
confidence: 99%